Candiduria in adults and children: prevalence and antifungal susceptibility in outpatient of Jataí-GO - Sousa, Izabela Alves De; Braoios, Alexandre; Santos, Thaynara Gonzaga; Lima, Juliano Alves De; Costa, Rafael Menezes Da (Sociedade Brasileira de Patologia ClínicaSociedade Brasileira de PatologiaSociedade Brasileira de Citopatologia, 2014)
Introduction: The term candiduria refers to the presence of yeast in urine and Candida albicans is the most common agent. In general, routine laboratories do not perform identification and cultivation of yeast. Objectives: To determine the prevalence of Candida species and to evaluate the antifungal susceptibility of the species isolated in urine of outpatients Jataí-GO, between January-October 2013. Material and method: Urine samples containing fungal structures were plated out on Sabouraud agar with chloramphenicol. Differentiation was taken with the urease test, nitrogen and carbon sources assimilation, germ tube test, morphology on cornmeal agar and chromogenic agar cultivation. Susceptibility was evaluated at antifungal itraconazole, fluconazole, amphotericin B and ketoconazole. Results: 1,215 urine tests were performed, and 64 had fungal structures (5.3%). Two samples were lost, thus here we considered 62 isolates. From this total, 43 were identified as C. albicans (67.2 %), eight C. glabrata (12.5 %), five C. krusei (7.8%), three C. tropicalis (4.7%), and three could not determine the species (4.7%). Amphotericin B and ketoconazole inhibited 94.9% of the isolates. On the other hand, 55.9% and 54.2 % were resistant to itraconazole and fluconazole, respectively. The resistance rates of both fluconazole and itraconazole for C. glabrata and C. albicans, as fluconazole for C. albicans and C. krusei, showed significant differences (p < 0.05). Conclusion: These data demonstrate the importance of conducting a full identification and susceptibility to antifungal agents in samples with yeast infection.

Introdução: O termo candidúria designa a presença de leveduras na urina e Candida albicans é o agente mais comum. Em geral, os laboratórios de rotina não realizam o cultivo e a identificação da levedura. Objetivos: Determinar a prevalência de espécies de Candida e avaliar o perfil de sensibilidade aos antifúngicos das espécies isoladas em urina de pacientes ambulatoriais do município de Jataí-GO, entre janeiro e outubro de 2013. Material e método: Amostras de urina que continham estruturas fúngicas foram semeadas em ágar Sabouraud com cloranfenicol. A diferenciação foi feita com provas da urease, assimilação de fontes de nitrogênio e carbono, tubo germinativo, morfologia em ágar fubá e cultivo em ágar cromogênico. Foi avaliada a sensibilidade aos antifúngicos itraconazol, fluconazol, anfotericina B e cetoconazol. Resultados: Foram realizados 1.215 exames de urina, sendo que 64 apresentaram estruturas fúngicas (5,3%). Houve perda de duas amostras, assim, considerou-se 62 isolados. Desse total, 43 foram identificadas como C. albicans (67,2%); oito, C. glabrata (12,5%); cinco, C. krusei (7,8%); três, C. tropicalis (4,7%); e em três não foi possível determinar a espécie (4,7%). Anfotericina B e cetoconazol inibiram 94,9% dos isolados. Por outro lado, 55,9% e 54,2%, respectivamente, apresentaram resistência a itraconazol e fluconazol. As taxas de resistência a itraconazol e fluconazol de C. glabrata e C. albicans e também do fluconazol entre C. albicans e C. krusei apresentaram diferenças significativas (p < 0,05). Conclusão: Os dados demonstram a importância de se realizar a identificação completa e também o antifungigrama para amostras que apresentam infecção por leveduras.
Candidúria em adultos e crianças: prevalência e suscetibilidade a antifúngicos em pacientes ambulatoriais de Jataí-GO
Keywords: antifungal susceptibility test; amphotericin B; Candida; candiduria; fluconazole; ketoconazole; itraconazole; antifungigrama; anfotericina B; Candida; candidúria; cetoconazol; fluconazol; itraconazol